The Relationship among Body Mass Index, Physical Activity, Dynamic Balance, and Sleep Patterns - Kananda, Geubrina; Megawati, Eka Roina (Universitas Pendidikan Indonesia, 2020)
According to the World Health Organization in 2010, overweight and obesity are the fifth risk factors of the cause of death in the world. Obesity is influenced by the level of physical activity and it could cause a disturbance in dynamic balance and induce sleep disorder known as sleep apnea. Meanwhile, the lack of physical activity also affects the dynamic balance that can increase the risk of fall injury during the dynamic physical activity. The aim of this study was to investigate the relationship among body mass index, physical activity, the dynamic balance, and sleep patterns. The subjects of this study were 72 young adults aged 20 years in average, consisted of 47 males and 25 females. The body mass index was undertaken by dividing the body weight (kg) and height in meter square (m2). The level of physical activity was performed by using the International Physical Activity Questionnaire. Meanwhile, the dynamic balance was measured by using the modified Bass test; while sleep patterns was measured by using the Pittsburgh Sleep Quality Index. This study found that there was a significant association between BMI and dynamic balance with p value = 0.006 (p 0.05); whereas physical activity was not significantly associated to the dynamic balance (p0.05). Meanwhile, body mass index and physical activity were not significantly associated to sleep patterns (p 0.05). This study concludes that body mass index has a significant association to dynamic balance. Meanwhile, dynamic balance is highly needed in carrying out dynamic physical activity to avoid fall injury.